2022
DOI: 10.3389/fbioe.2022.804201
|View full text |Cite
|
Sign up to set email alerts
|

Graphene-Based Nanomaterials for Dental Applications: Principles, Current Advances, and Future Outlook

Abstract: With the development of nanotechnology, nanomaterials have been used in dental fields over the past years. Among them, graphene and its derivatives have attracted great attentions, owing to their excellent physicochemical property, morphology, biocompatibility, multi-differentiation activity, and antimicrobial activity. In our review, we summarized the recent progress about their applications on the dentistry. The synthesis methods, structures, and properties of graphene-based materials are discussed. Then, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 155 publications
(188 reference statements)
0
22
0
Order By: Relevance
“…(3696) Many trials have been suggested in order to decrease this polymerization shrinkage such as incremental packing of the resin composite restorations, soft-start light curing method, changing in the chemistry of the resin matrix, incorporation of higher fillers content and using of indirect resin composite restorations 2,3 . One of the newly introduced nanofillers in the medical and dental field is the graphene oxide [11][12][13] . Graphene oxide reported an improvement in the mechanical properties of polymeric materials 13,14 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…(3696) Many trials have been suggested in order to decrease this polymerization shrinkage such as incremental packing of the resin composite restorations, soft-start light curing method, changing in the chemistry of the resin matrix, incorporation of higher fillers content and using of indirect resin composite restorations 2,3 . One of the newly introduced nanofillers in the medical and dental field is the graphene oxide [11][12][13] . Graphene oxide reported an improvement in the mechanical properties of polymeric materials 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Graphene oxide contains oxygen atoms bonded to carbon atoms and contains many functional groups at its surface such as oxygen, epoxide, carbonyl, phenyl and hydroxyl groups. However, reduced graphene oxide can be considered as an intermediate structure between the purely-carbon graphene and highly-oxidized graphene oxide 11,12 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several substances, including proteins, peptides, microRNA, hydroxyapatite, calcium phosphate, antibiotics, silver nanoparticles, etc., as well as other combinations of these, are being investigated for use as implant coatings to enhance dental applications. From these, graphene oxide and its derived materials have proved benefit in biological applications, and in recent years, the number of studies looking at graphene and its derivatives as a reinforcing phase in composite coatings has been growing quickly [136] …”
Section: Biomedical Applicationsmentioning
confidence: 99%
“…Additionally, graphene was a material of choice for various dental applications such as in bone grafting, tissue engineering, pulp and periodontium regeneration, dental cements and adhesives, resins, whitening agents, dental implants collagen membranes, and biomarkers of oral saliva. The use of graphene in dentistry resulted in enhanced positive outcomes, but its manufacturing for industrial purposes was quite challenging and time-consuming [ 173 ]. This was an initial step that opened a gateway to the incorporation of other biocompatible and cost-effective nanomaterials in the future nanodentistry.…”
Section: The Titanium Oxide Npsmentioning
confidence: 99%